Technical analysis: The psychology of the market of dry bulk freight rates - Joan Mileski; Christopher Clott; Cassia Bömer Galv\~ao; Taliese Laverne (Journal of Shipping and Trade (JST), 2020)
Financial technical analysis of markets and trends differs from fundamental analysis in that econometrics are used on "fundamental" economic data in fundamental analysis. Technical analysis, however, adds to the overall trend analysis an additional examination of the psychology of markets. For freight rate predictions, there has been an exclusive reliance on typical fundamental analysis. Our results indicate that adding technical analysis to freight rate prediction can provide a better overall result. Psychological forces such as "irrational exuberance" or severe bearishness can influence trend predictions making them at best incomplete and at worst inaccurate for predicting the demand for shipping services. Further, ship construction decisions use freight rate predictions. In this paper, we perform a 20-year technical analysis of the BDI/Baltic Dry Index (formerly BFI/Baltic Freight Index) This analysis is a better, richer evaluation of freight rate trends that influence ship construction. Furthermore, technical analysis requires specific in-depth knowledge of the psychology of the market and experience in this type of trend analysis.
Keywords: 650; Baltic dry index; Freight rate forecasting; Psychological analysis; Technical analysis